Crystal chemistry of vanadium-bearing ellestadite waste forms - Fang, Yanan (2020)
Vanadate ellestadites Ca10(SiO4) x(VO4)6-2 x(SO4) xCl2, serving as prototype crystalline matrices for the fixation of pentavalent toxic metals (V, Cr, As), were synthesized and characterized by powder X-ray and neutron diffraction (PXRD and PND), electron probe microanalysis (EPMA), Fourier transform infrared spectroscopy (FTIR), and solid-state nuclear magnetic resonance (SS-NMR). The ellestadites 0.19 < x < 3 adopt the P63/ m structure, while the vanadate endmember Ca10(VO4)6Cl2 is triclinic with space group P1̅. A miscibility gap exists for 0.77 < x < 2.44. The deficiency of Cl in the structure leads to short-range disorder in the tunnel. Toxicity characteristic leaching testing (TCLP) showed the incorporation of vanadium increases ellestadite solubility, and defined a waste loading limit that should not exceed 25 atom % V to ensure small release levels.